Hyperalgesia induced by low-dose opioid treatment before orthopaedic surgery. Issue 4 (April 2015) - Hina, Nabil; Fletcher, Dominique; Poindessous-Jazat, Frédérique; Martinez, Valéria
<x xml:space="preserve">Abstract</x> BACKGROUND Chronic pain and opioid consumption may trigger diffuse hyperalgesia, but their relative contributions to pain vulnerability remain unclear. OBJECTIVES To assess preoperative opioid-induced hyperalgesia and its postoperative clinical consequences in patients with chronic pain scheduled for orthopaedic surgery. DESIGN A prospective observational study. SETTINGS Raymond Poincare teaching hospital. PATIENTS Adults with or without long-term opioid treatment, scheduled for orthopaedic surgery. PRIMARY OUTCOME MEASURE Preoperative hyperalgesia was assessed with eight quantitative sensory tests, in a pain-free zone. SECONDARY OUTCOME MEASURES Postoperative morphine consumption and pain intensity were evaluated using a numerical rating scale (NRS) in the recovery room and during the first 72 h. RESULTS We analysed results from 68 patients (28 opioid-treated patients and 40 controls). Mean daily opioid consumption was 42 ± 25 mg of morphine equivalent. The opioid-treated group displayed significantly higher levels of preoperative hyperalgesia in three tests: heat tolerance threshold (47.1°C vs. 48.4°C; P = 0.045), duration of tolerance to a 47°C stimulus (40.2 vs. 51.1 s; P = 0.03) and mechanical temporal summation [1.79 vs. 1.02 (ΔNRS10–1); P = 0.036]. Patients in the opioid-treated group consumed more morphine (19.1 vs. 9.38 mg; P = 0.001), had a higher pain intensity (7.6 vs. 5.5; P = 0.001) in the recovery room and a higher cumulative morphine dose at 72 h (39.8 vs. 25.6 mg; P = 0.02). CONCLUSION Chronic pain patients treated with low doses of opioid had hyperalgesia before surgery. These results highlight the need to personalise the management of patients treated with opioids before surgery. TRIAL REGISTRATION ID-RCB 2011-A00304-37.